Status Keharaman Produk yang Mendukung Agresi Israel terhadap Palestina (Studi Analisis Fatwa MUI No. 83 Tahun 2023) - Fachrudin Fachrudin; Khaerul Aqbar; Rachmat Bin Badani Tempo (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research aims to understand and analyze the Indonesian Ulema Council (Majelis Ulama Indonesia, MUI) Fatwa number 83 of 2023 regarding the prohibition status of products that support Israel's aggression against Palestine. The issue addressed in this study is: how does the analysis of MUI Fatwa no. 83 of 2023 relate to the prohibition status of products that support Israel's aggression against Palestine. This study is a literature review (library research) utilizing a qualitative descriptive method and employing normative juridical and conceptual approaches. The research findings are as follows: MUI Fatwa number 83 of 2023 establishes that all forms of support for the Palestinian struggle are mandatory, while actions, whether direct or indirect, that support Israel's aggression are deemed forbidden. The status of prohibition on products supporting Israel's aggression against Palestine in Islamic jurisprudence is known as "haram li ghairihi," meaning prohibited due to external factors beyond the nature of the product itself, not its intrinsic substance. In this case, it pertains to cooperation and support for Israel's criminal actions. Therefore, the original status of the product is halal, but if there are actions clearly contrary to Islamic teachings, such as human rights violations or support for Israel's aggression against Palestine, then it is deemed haram or prohibited in Islam.